2016
DOI: 10.1152/ajpregu.00352.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nax signaling evoked by an increase in [Na+] in CSF induces water intake via EET-mediated TRPV4 activation

Abstract: -Water-intake behavior is under the control of brain systems that sense body fluid conditions at sensory circumventricular organs (sCVOs); however, the underlying mechanisms have not yet been elucidated in detail. Na x is a sodium (Na ϩ ) level sensor in the brain, and the transient receptor potential vanilloid (TRPV) channels TRPV1 and TRPV4 have been proposed to function as osmosensors. We herein investigated voluntary water intake immediately induced after an intracerebroventricular administration of a hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…II.7E). In addition, prof. Noda's laboratory recently found that Na x signals were also involved in the immediate induction of water intake evoked by an intracerebroventricular administration of a hypertonic NaCl solution (Sakuta et al, 2016); Here, Na x in the OVLT appears to mediate this function (unpublished observation in prof. Noda's laboratory). Moreover, activation of OVLT neurons expressing vasopressin receptor 1a is reported to be involved in water intake to prevent anticipatory thirst during sleep period (Gizowski et al, 2016).…”
Section: Ii4 Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…II.7E). In addition, prof. Noda's laboratory recently found that Na x signals were also involved in the immediate induction of water intake evoked by an intracerebroventricular administration of a hypertonic NaCl solution (Sakuta et al, 2016); Here, Na x in the OVLT appears to mediate this function (unpublished observation in prof. Noda's laboratory). Moreover, activation of OVLT neurons expressing vasopressin receptor 1a is reported to be involved in water intake to prevent anticipatory thirst during sleep period (Gizowski et al, 2016).…”
Section: Ii4 Discussionmentioning
confidence: 95%
“…receptor-positive neurons may be also involved in water-intake control, and that some other water neurons are also present in the SFO and OVLT, which are activated by signals of Na + , osmolality, or other dipsogenic hormones (Fitzsmons, 1998;Li et al, 2003;Sakuta et al, 2016). Under the Na-depleted condition (right), salt neurons which innervate the vBNST are activated by Ang II and enhance salt appetite.…”
Section: Chapter V Summary and Conclusionmentioning
confidence: 99%
“…As expected, lactate enhanced the H + -induced activation of OVLT(/PVN) neurons ( Figure 4F). Notably, the Na x signal may lead to the production of epoxyeicosatrienoic acids (EETs) in the OVLT through the activation of the AA cascade (Sakuta et al, 2016). Since treatments with hyperosmotic mannitol solution did not activate pH-sensitive OVLT(/PVN) neurons ( Figure 4G), osmotic changes (induced by hypertonic Na solution) did not appear to activate ASIC1a-positive OVLT(/PVN) neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the SFO is the principal site for sensing [Na + ] in body fluids by Na x to control salt appetite (Hiyama et al, 2004;Matsuda et al, 2017). Our recent findings suggested that the Na x signal in sCVOs is also involved in water-intake control (Sakuta et al, 2016). However, possible roles for Na x in BP control have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the low GFR due to a decrease in the circulating blood caused by low body Na + content increases renin release, leading to elevation of body Na + content due to an increase in Na + reabsorption via aldosterone-induced increases of ENaC production and surface expression in the collecting duct. Further, recently Na x has been reported to be a Na + concentration-sensitive Na + channel acting as a Na + sensor (46)(47)(48)(49)(50)(51)(52)(53)60,61). Na x was found in the brain as an atypical Na + channel, poorly homologous to the voltage-gated Na + channels (62).…”
mentioning
confidence: 99%